Is Somatization Escape From Stigmatization? A Cross-Sectional Study - Kaçan, Havva; Ateş, Sebahat; Üstün, Besti (Gumushane University, 2024)
Somatization is a psychiatric condition characterized by repetitive bodily symptoms that cannot be fully explained by the medical condition of the individual and cannot be attributed to another mental disorder. This research aims to examine the relationship between the somatic symptoms of nursing students and their tendency to stigmatize. The research was conducted at two different universities and a total of 438 students participated. The data were collected using the personal information form, the "Somatization" subscale of the SCL-90-R scale, and the Stigma Tendency Scale. The average score of somatization of students was 0.98±0.70 and the average score of Stigma Tendency Scale was 45.39±11.69. It was found that female students, those who did not share their problems, those who had previously applied to a psychiatrist or psychologist and received mental therapy, those who took medication, those who recently felt the need for a psychiatrist or psychologist, students with a diagnosis of mental illness in their family and who knew about mental health and diseases had more somatic problems (P
Keywords: Nursing Students; Stigma; Somatization; 4. Education; 3. Good health